2008
DOI: 10.1080/14623940802207022
|View full text |Cite
|
Sign up to set email alerts
|

Peer support groups: fostering a deeper approach to learning through critical reflection on practice

Abstract: Twenty part-time first year foundation degree students and two tutors in an English higher education institution engaged in an internally funded collaborative action research project. We explored the establishment of peer support groups to support students' reflection on practice, based on the 10 principles of reflective practice described by Ghaye and Ghaye in 1998. Over 10 weeks the tutor and students engaged in weekly peer group discussions focusing on students' developmental understanding and use of each p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…In one qualitative study, Devenish et al (2009) found doctoral student participation in a support group was associated with perceptions that the members were developing the relational collaboration skills necessary to fulfill professional roles in academia. Furthermore, Bold (2008) suggested participation in support groups related to coursework provided an opportunity for greater reflective capacity among students which resulted in deeper learning and greater integration of material. Although the authors of these aforementioned studies have advocated for the increased implementation of support groups during academic preparation, there has remained a paucity of literature regarding their utility among counselor education students enrolled in doctoral statistics coursework.…”
Section: Peer-to-peer Support Groups In Higher Education Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…In one qualitative study, Devenish et al (2009) found doctoral student participation in a support group was associated with perceptions that the members were developing the relational collaboration skills necessary to fulfill professional roles in academia. Furthermore, Bold (2008) suggested participation in support groups related to coursework provided an opportunity for greater reflective capacity among students which resulted in deeper learning and greater integration of material. Although the authors of these aforementioned studies have advocated for the increased implementation of support groups during academic preparation, there has remained a paucity of literature regarding their utility among counselor education students enrolled in doctoral statistics coursework.…”
Section: Peer-to-peer Support Groups In Higher Education Settingsmentioning
confidence: 99%
“…Several researchers investigated the utility of peer-to-peer support approaches in higher education settings (Anderson et al, 2000; Bold, 2008; Devenish et al, 2009; McGrail, Rickard, & Jones, 2006; Page-Adams, Cheng, Gogineni, & Shen, 1995). For example, Page-Adams, Cheng, Gogineni, and Shen (1995) noted doctoral students participating in a writing support group developed, submitted, or published more scholarly manuscripts (87%) when compared to a control group (20%).…”
Section: Peer-to-peer Support Groups In Higher Education Settingsmentioning
confidence: 99%
“…Other methods described in the literature include personal accounts of drawing (Tokolahi, 2010); reflective conversations (Simpson and Trezise, 2011); conversation communities (McCormack and Kennelly, 2011); student peer support groups (Bold, 2008); shared reflective blogs (Boulton and Hramiak, 2012); workshops (Gardner, 2009); team coaching sessions (Richards, Mascarenhas and Collins, 2009); workplace group exercises (Langer, 2001); and 'dialog cafés' (Thunberg, 2011). Drawings and photographs provide a dynamic and flexible medium to express complex situations, allowing new insights to emerge (Tokolahi, 2010;Shepherd, 2006).…”
Section: Other Methods Of Reflectionmentioning
confidence: 99%
“…Several papers have recommended this (Sen, 2010;Roberts, 2009;Bold, 2008). It may be that those who find reflection difficult are unaware of different methods which can be used, such as drawing, or reflecting with others, which they may find more suitable for them.…”
Section: The Value Of Reflection As a Professional Toolmentioning
confidence: 99%
“…Informed by Dewey's (1933) classic early observations on the inherent usefulness of reflective learning, the assessment tasks were structured to encourage reflective learning. The aim of the reflective practice activities was both to encourage deep learning (Bold 2008) and to prepare students for the demands of the professional workplace (Chen et al 2009) through collaborative learning in groups (Thomas 2014) using e-learning technology.…”
Section: Monitoring Collaborationmentioning
confidence: 99%